Visual Culture Analysis in Campaign of Covid-19 - Vivi Varlina; Yasraf Amir Piliang; Ruly Darmawan; Tri Sulistyaningtyas (JURNAL SOSIAL HUMANIORA (JSH), 2023)
In the contemporary context, the significance of utilizing online media as an information portal cannot be overstated. This importance is particularly pronounced during the Covid-19 pandemic, as people actively seek information through online platforms to meet their informational requirements. The primary objective of this research is to investigate the visual elements employed in Covid-19 campaigns, with each element carrying meaningful representations. To accomplish this, the researcher employs visual culture studies to analyze Covid-19 campaigns from a neurophysiological perspective. The methodology involves employing a semantic differential scale and principal components analysis (PCA) with the participation of 22 respondents, who assess 12 binary paired adjective concepts. The analysis centers on four images sourced from the online media platform www.covid19.go.id. The findings indicate that people perceive visual objects influenced by technology in a manner that involves recognition. Each visual element serves as a representation of knowledge and is linked to specific ideas. From a modern neurophysiological standpoint, technology-mediated visual elements lead to logical and constructive outcomes while exhibiting unique affordabilities. These research findings impart valuable insights to the Government of Indonesia, underscoring the importance of considering physiological, affective, and aesthetic aspects of visual elements in formulating their pandemic campaign policies